Faktor Risiko Sanitasi Lingkungan terhadap Kejadian Stunting pada Balita di Indonesia : Literatur Review - Rahmi Lisdeni; Budi Hartono (Poltekkes Kemenkes Padang, 2023)
Stunting in toddlers is a global issue, according to WHO, 2022 that report there are 149,2 million toddlers who suffer from stunting. The research method is systematic literature review. The aim of the study is to look at the relationship between STBM theory, personal hygiene, and diarrhea with the incidence of stunting in toddlers. Based on the results of the study that in general there is a significant relationship between environmental sanitation variables and the incidence of stunting in toddlers. The results based on the specific research objectives found that the CTPS variable had a significant relationship with the incidence of stunting in toddlers, namely the research by Maudy Risma Slodia, et al, 2022 and Yuliani Soerachmad,et al, 2019. Variables of clean water facilities that are significantly related to the incidence of stunting in toddlers are research by Maudy Risma Slodia, et al 2022, Zairinayati, et al, 2019 and Inamah,et al, 2021. Conclusion : The environmental sanitation variables that affect stunting are CTPS, household waste protection, household rubbish protection, household drinking water and food security, toilet ownership facilities, incidence of diarrhea, availilability of clean water facilities, etc. Suggestion : expected that this research will become input for the community and health workers to control risk factors for environmental sanitation in order to reduce stunting in Indonesia.